FORMULASI DAN UJI AKTIVITAS ANTIBAKTERI GEL HAND SANITIZER EKSTRAKETANOL DAUN WARU (Hibiscus tiliaceus L) TERHADAP Escherichia coli DAN Staphylococcus epidermidis - Imran Firman; Richo Sahetapy (Universitas Pahlawan Tuanku Tambusai, 2023)
Waru leaves have been shown to have antioxidant, anti-inflammatory, antiemetic, and antibacterial properties that are efficacious as a fever reliever, ulcer treatment, and tonsillitis treatment. The purpose of this study was to determine the antibacterial activity as well as to formulate and evaluate antiseptic gel preparations (hand sanitizer) from hibiscus leaf extract (Hibiscus tiliaceus L) against parameters namely organoleptic test, homogeneity test, pH test, viscosity test. The extraction method used is the maceration method using 96% ethanol as solvent. The results of the phytochemical screening study were positive containing flavonoids, tannins, saponins and phenols. Physical stability of hand sanitizer gel preparations ethanol extract of waru leaves (Hibiscus tiliaceus L) effective in inhibiting Staphylococcus epidermidis and Escherichia coli bacteria, the most effective in inhibiting FIII at a concentration of 15% with the resulting inhibition zone value of 17.3 mm for Staphylococcus epidermidis bacteria and 18.8 mm for Escherichia coli bacteria. Keywords : Gel, hand sanitizer, hibiscus leaf, Escherichia coli, Staphylococcus epidermidis